Why employees and managers engage in unethical practices - Boomsma, Dorret I (2018)
The scope of this paper is to investigate the reasons as to why employees and managers in the workplace engage willingly in unethical practices. The paper begins by exploring the concept of ethics in the corporate world. It further highlights the different forms of unethical practices in the various companies in the contemporary world. The various theories that explore the issue of unethical practices in the workplace are highlighted and how they relate to the occurrence of unethical demeanor. The social contract theory and the psychological theories are highlighted in the paper. The study further delves in exploring the various types of reasons as depicted in different forms of literature in the world. The reasons include the pressure for performance at work, the effect of groupthink in the workplace, pressure from management, management control, demographic factors, and psychological traps, broken window theory. The paper also recommends the executive techniques that can be used to curb the psychological traps in the corporations. The paper also explores the broken window theory as a cause for unethical practices in the workplace. In conclusion, the paper comes up with recommendations for corporations